CC chemokine receptors and chronic inflammation--therapeutic opportunities and pharmacological challenges. - White, G; Iqbal, A; Greaves, D (American Society for Pharmacology and Experimental Therapy, 2013)
Chemokines are a family of low molecular weight proteins with an essential role in leukocyte trafficking during both homeostasis and inflammation. The CC class of chemokines consists of at least 28 members (CCL1-28) that signal through 10 known chemokine receptors (CCR1-10). CC chemokine receptors are expressed predominantly by T cells and monocyte-macrophages, cell types associated predominantly with chronic inflammation occurring over weeks or years. Chronic inflammatory diseases including rheumatoid arthritis, atherosclerosis, and metabolic syndrome are characterized by continued leukocyte infiltration into the inflammatory site, driven in large part by excessive chemokine production. Over years or decades, persistent inflammation may lead to loss of tissue architecture and function, causing severe disability or, in the case of atherosclerosis, fatal outcomes such as myocardial infarction or stroke. Despite the existence of several clinical strategies for targeting chronic inflammation, these diseases remain significant causes of morbidity and mortality globally, with a concomitant economic impact. Thus, the development of novel therapeutic agents for the treatment of chronic inflammatory disease continues to be a priority. In this review we introduce CC chemokine receptors as critical mediators of chronic inflammatory responses and explore their potential role as pharmacological targets. We discuss functions of individual CC chemokine receptors based on in vitro pharmacological data as well as transgenic animal studies. Focusing on three key forms of chronic inflammation--rheumatoid arthritis, atherosclerosis, and metabolic syndrome--we describe the pathologic function of CC chemokine receptors and their possible relevance as therapeutic targets.